Genetic markers cannot determine Jewish descent - Falk, Raphael (Frontiers in Genetics, 2015)
Social interaction is a basic property of human Darwinian evolution. Presumably inherent differential physical as well as behavioural properties have always been criteria for identifying friend or foe. Yet, biological determinism is a relatively modern term, and scientific racism is, oddly enough, largely a consequence or a product of the Age of Enlightenment and the establishment of the notion of human equality. In recent decades ever-increasing efforts and ingenuity were invested in identifying Biblical Israelite genotypic common denominators by analysing assorted phenotypes, like facial patterns, blood types, diseases, DNA-sequences, and more. It becomes overwhelmingly clear that although Jews by their socio-religious-cultural relationship maintained also considerable consanguinity, there is no Jewish genotype to identify.